FREQUENCY OF IMMUNODEFICIENCY CONDITIONS IN FREQUENTLY ILL CHILDREN - Khadjaev Tokhir Avazkhanovich (Ethiopian International Journal of Multidisciplinary Research, 2025)
Recurrent or prolonged infections are major indicators of primary immunodeficiencies; although most frequently ill children have normal immune function, early detection of hidden immunodeficiencies is critical for improving patient outcomes. In this study, the frequency of immunodeficiency conditions was evaluated in 83 children aged 1 to 7 years with recurrent infections. Immunological screening included assessment of lymphocyte subpopulations, serum levels of IgA, IgM, IgG, IgE, and phagocytic activity of neutrophils. Immunodeficiency was identified in approximately 46–47% of the patients: about 12% of cases were classified as primary immunodeficiencies, and 34–35% were secondary. The most common immune disturbances were selective IgA deficiency, T-cell function impairment, and defects in neutrophil phagocytic activity. The findings highlight the importance of immunological screening in frequently ill children for early diagnosis and timely intervention.